THE STRUCTURE OF THE TENSE FUNCTIONAL-SEMANTIC FIELD IN THE ENGLISH LANGUAGE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article explores the structure of the functional-semantic field of tense in the English language. Drawing from functional grammar theories, it examines how tense as a semantic category is represented across morphological, syntactic, lexical, and contextual levels. Special attention is paid to how the temporal meanings are conveyed by various linguistic elements and their hierarchical positions within the field — from core morphological categories to peripheral lexical items. The study also considers cross-linguistic observations, the concept of universality of temporal semantics, and distinctions in expression across languages.